Recent Investigations of the First Bleeder Family in Åland (Finland) Described by von Willebrand - Nyman, D; Eriksson, A W; Blombäck, M; Frants, R R; Wahlberg, P (Thrombosis and Haemostasis, 1981)
The still living members of the original bleeder family on the Åland Islands described by von Willebrand in 1926 have been reinvestigated by using modem laboratory techniques for the measurement of the Factor VIII complex and with regard to platelet aggregation. The low level of F VIII: C activity demonstrated in 1957 could be confirmed in some of the family members, who however all had only mild bleeding symptoms. More consistently, in 6 out of 10, a low F VIIIR: Ag was found; all of those also had a low F VIII: RCoF. In none of the members were excessively low values for any of the parameters found. However, the spectrum of the whole F VIII complex indicates that the original family described by von Willebrand belongs to von Willebrand’s disease, type I.
Keywords: von Willebrand’s disease; Åland Islands; Original family; F Vlll-complex; Platelet aggregation; Genetics